Upaya Sosialisasi oleh Komisi Pemilihan Umum terhadap Peningkatan Peran Masyarakat dalam Pembangunan Politik di Kota Palangka Raya - Indah Tri Handayani; Wiwik Suprapti (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2015)
Socialization efforts by the Electoral Commission This study aims to determine the extent of the socialization efforts carried out by the Regional General Election Commission of the City of Palangka Raya towards increasing the role of the community in political development in the City of Palangka Raya. The type of research used is qualitative descriptive. Data sources come from primary data and secondary data. Data collection techniques are documentation, observation, and interviews. Based on the results and discussion it can be explained that efforts to increase the role of the community in political development in the City of Palangka Raya by the Regional Election Commission, include (a) Simulation, voting procedures at polling stations in the Legislative Election, (b) Sympathetic Actions, dividing the Legislative Election flyers to citizens, (c) Seminars, activities which include simulations and sympathetic actions, (d) Technical guidance, methods for implementing the Legislative Election. Based on the recapitulation data on the calculation of the vote results of Political Parties and Candidates for Regional Representatives, the House of Representatives and the Election Regional Representatives as a whole as follows: Elections remain 141,028 people, those who use voting rights are 95,584 people, who do not exercise their right to vote 45,444 people . Seeing the efforts and results that were achieved by the General Election Commission of Palangka Raya City. In this case, the Palangka Raya City KPU as the organizer of the election has a large role in political development in the City of Palangka Raya. Evidenced from the community's role in using their right to vote in general elections.